2006
DOI: 10.1364/oe.14.008974
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of generalized vector Helmholtz-Gauss beams through paraxial optical systems

Abstract: Abstract:We introduce the generalized vector Helmholtz-Gauss (gVHzG) beams that constitute a general family of localized beam solutions of the Maxwell equations in the paraxial domain. The propagation of the electromagnetic components through axisymmetric ABCD optical systems is expressed elegantly in a coordinate-free and closed-form expression that is fully characterized by the transformation of two independent complex beam parameters. The transverse mathematical structure of the gVHzG beams is form-invarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…This possibility has been analyzed in many publications [8][9][10][11] where examples are included. Again, the full discussion of this problem is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This possibility has been analyzed in many publications [8][9][10][11] where examples are included. Again, the full discussion of this problem is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 99%
“…The produced wavefronts can travel long distances or go through an optical system without the diffraction changes experienced by ordinary wavefronts [8][9][10][11]. For the validity of this statement we refer to the cited references and to the pertaining literature cited in those studies.…”
Section: Description Of the Experimental Proceduresmentioning
confidence: 99%
“…It was first suggested in reference [15] that the number of ring dislocations appearing in the cross correlation function are in a one to one correspondence with the topological charge of a partially coherent vortex. This assertion was reported later in 2012 by Yang et al 10 Following the theoretical results reported in our previous works 9, 15 and also those given by Yang et al 10 suggesting that the singularities in the CCF of a partially coherent OV are directly related to the topological charge, we designed an experimental setup to demonstrate this direct relationship between the topological charge in a partially coherent vortex and the number of ring dislocations present in the CCF.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation properties of several beams in GRIN lenses are discussed by researchers via the approach of Fractional Fourier transform (FrFT), such as cosh-Gaussian beams, Ince-Gaussian beams, HelmholtzGauss beams and etc. [5][6][7][8][9][10][11][12][13] . The FrFT approach treats the GRIN lens as a single-lens equivalent optical system of FrFT, which adopts the approximation of the first-order optics.…”
Section: Introductionmentioning
confidence: 99%